2000
DOI: 10.1159/000012131
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index Determines the Success of Lymph Node Dissection and Predicts the Outcome of Gastric Carcinoma Patients

Abstract: We tried to determine the role of the body mass index (BMI) on the extent of lymph node dissection in gastric cancer surgery. Seven hundred and eighty-seven patients with gastric carcinoma were reviewed. Ninety-two (11%) patients exceeded the upper limit of the optimum BMI. Significantly fewer lymph nodes were removed following D2 (p = 0.002) and ≥D3 (p = 0.023) dissections, and the lymph node ratio was significantly (p = 0.0383) higher in overweight patients. The recurrence-free survival was significantly (p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
134
5
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(146 citation statements)
references
References 16 publications
5
134
5
1
Order By: Relevance
“…Some studies have reported the effect of obesity on open gastric cancer surgery. The Japanese studies by Inagawa et al [15] and Dhar et al [11] have shown that obesity may cause an increased rate of postoperative complications and a poor prognosis. In contrast, other studies, done in Europe by Gretschel et al [16] and Barry et al [17], have shown that obesity does not affect postoperative complications, nor does it lead to a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have reported the effect of obesity on open gastric cancer surgery. The Japanese studies by Inagawa et al [15] and Dhar et al [11] have shown that obesity may cause an increased rate of postoperative complications and a poor prognosis. In contrast, other studies, done in Europe by Gretschel et al [16] and Barry et al [17], have shown that obesity does not affect postoperative complications, nor does it lead to a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report from Japan concluded that a higher BMI hampered the performance of lymphadenectomy during gastric cancer surgery, and a higher BMI was reported as an independent predictor of cancer recurrence [11]. However, there are only a few studies of the relationship between obesity and laparoscopy-assisted radical gastrectomy.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the Japan Clinical Oncology Group (JCOG) 9501 study, which compared D2 and D2 plus para-aortic LN dissections among gastric cancer patients, only obesity and age were identified as significant patient-related factors associated with major surgical complications [6,18]. Many largescale studies have repeatedly demonstrated that obesity influences surgical outcomes after gastric cancer surgery [7,[19][20][21]. Conversely, studies focusing on LAG have shown that obesity does not increase surgical morbidity [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…We have subsequently demonstrated that similar results can be achieved in a large British district general hospital Barry et al, 2003). Despite these favourable reports, there remains a widely held assumption, that poor outcomes after surgery for gastric cancer in Britain are due to the greater age, comorbidity, advanced stages of disease and greater body mass indices of Western patients when compared with their Japanese counterparts (Dhar et al, 2000). Furthermore, most oesophagogastric cancer surgery in Britain and much of the West, has by tradition, been performed by general surgeons.…”
mentioning
confidence: 99%